2017
DOI: 10.1016/j.ejphar.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

New prodrugs of metformin do not influence the overall haemostasis potential and integrity of the erythrocyte membrane

Abstract: Although metformin, an oral anti-diabetic drug, has been found to have multidirectional effects over the past decade, it is characterised by unfavourable pharmacokinetic properties. This study discusses the effects of metformin, phenformin and three prodrugs of metformin on the haemostasis and integrity of Red Blood Cells (RBCs). The influence of examined biguanide derivatives on haemostasis was evaluated spectrophotometrically by clot formation and lysis test (CL-test) at 405nm. The extrinsic and intrinsic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 37 publications
(51 reference statements)
2
30
0
Order By: Relevance
“…All other synthesized compounds contributed to the significant increase in APTT and TT. Results presented in this study as well as those obtained in a previous one [ 22 ], in which metformin did not appear to affect APTT and PT, revealed that benzenesulfonamides with methyl substituents in the aromatic ring significantly affected the intrinsic coagulation pathway and the process of fibrin polymerization, and thus, may exert beneficial effects on plasma hemostasis. Importantly, also other sulfonamide-based metformin analogs, such as those with an o - or p -nitro substituent in the aromatic ring exert highly beneficial anti-coagulation properties, manifested by prolonged PT and APTT [ 41 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…All other synthesized compounds contributed to the significant increase in APTT and TT. Results presented in this study as well as those obtained in a previous one [ 22 ], in which metformin did not appear to affect APTT and PT, revealed that benzenesulfonamides with methyl substituents in the aromatic ring significantly affected the intrinsic coagulation pathway and the process of fibrin polymerization, and thus, may exert beneficial effects on plasma hemostasis. Importantly, also other sulfonamide-based metformin analogs, such as those with an o - or p -nitro substituent in the aromatic ring exert highly beneficial anti-coagulation properties, manifested by prolonged PT and APTT [ 41 ].…”
Section: Discussionsupporting
confidence: 84%
“…Only a derivative with a propyl chain in the aromatic ring (compound 5 ) at a concentration of 1.5 µmol/mL contributed to hemolysis reaching the value of 9.99 ± 2.95%. In our previous study, metformin did not exert any effect on the integrity of erythrocyte membrane over the entire concentration range (0.006–1.5 µmol/mL) [ 22 ]. For instance, one-hour incubation of human RBC with metformin at 1.5 µmol/mL resulted in 1.81 ± 0.78% hemolysis [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin, and its derivatives 1-4 were tested at the concentration range 0.006-1.5 µmol/mL, based on therapeutic plasma concentration of metformin (0.129 to 90 mg/L [38], which is 0.8 nmol/mL-0.6 µmol/mL) as well as our previous studies [32,34]. The exception was cell viability studies, where higher concentrations were used to determine IC 50 values.…”
Section: Tested Compoundsmentioning
confidence: 99%
“…Sulfonamide-based compounds ( Figure S1, Supplementary Materials) were found to exhibit beneficial effects on plasma, vascular and platelet haemostasis, which is frequently impaired in T2DM patients [32][33][34]. For instance, o-nitrobenzenesulfonamide was found to demonstrate more prominent effects on certain plasma and vascular haemostasis parameters than the parent drug metformin [32][33][34]. The beneficial effects of sulfenamide and sulfonamide derivatives of metformin on plasma and vascular haemostasis have been summarized in Figure S1 (Supplementary Materials).…”
Section: Introductionmentioning
confidence: 99%